Kualitas Pupuk Kompos Padat Yang Dihasilkan Dari Pemanfaatan Larva Black Soldier Fly (Hermetie Illucencs L) Di Sahabat Bank Sampah Alam Kota Pariaman: The Quality of Solid Compost Fertilizer Produced from The Utilization of Black Soldier Fly Larva (Hermetie Illucencs L) At Sahabat Natural Waste Bank, Pariaman City - Muhelni, Leila; Betrisnawiwi, Betrisnawiwi; Junialdi, Rezi; Mukhtar, Dertha (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Indonesia is the 4th most populous country in the world. The main factors influencing the high rate of urban population growth are urbanization and migration. This condition causes an increase in the amount of waste generation, whether solid, liquid or gas waste. Therefore, efforts are needed to manage and process waste generation, one of which is composting. Composting is a form of reuse and recovery of resources from solid waste by decomposing organic matter with the help of organisms. One of the organisms that can be used as a waste decomposition agent is the Black Soldier Fly larvae. The composting process requires several requirements to produce good quality compost, namely the content of macro nutrients, namely N, P, K. This research was conducted on 3 February – 2 March 2022 at the Sahabat Alam Waste Bank (SAWB) Kp. Apar, South Pariaman, Pariaman City, West Sumatra. Sample testing was carried out at the Chemistry Laboratory of FMIPA UNP using the levels of Nitrogen (N) (Kjehdahl Method), Phosphorus (P) and Potassium (K) (X-Ray Fluorescence Method). The quality of N, P, K solid compost obtained from this study was nitrogen levels 6.09% (S.Week 1) and 9.324%, phosphorus levels 8.113% (S.Week 1) and 6.176% (S.Week 2), and 29.759% (S.Week 1) and 38.181% (S. .Week 2) for potassium levels.